Changes in standing stability with balance‐based torso‐weighting with cerebellar ataxia: A pilot study. (20th November 2019) - Widener, Gail L.; Conley, Nicole; Whiteford, Sarah; Gee, Jason; Harrell, Anthony; Gibson‐Horn, Cynthia; Block, Valerie; Allen, Diane D.
Abstract: Objectives: People with cerebellar ataxia have few options to improve the standing stability they need for function. Strategic placement of light weights on the torso using the balance‐based torso‐weighting (BBTW) method has improved stability and reduced falls in people with multiple sclerosis, but has not been tested in cerebellar ataxia. We examined whether torso‐weighting increased standing stability and/or functional movement in people with cerebellar ataxia. Methods: Ten people with cerebellar ataxia and 10 matched controls participated in this single‐session quasi‐experimental pilot study. People with ataxia performed the Scale for the Assessment and Rating of Ataxia (SARA) prior to clinical testing. All participants donned inertial sensors that recorded postural sway; stopwatches recorded duration for standing and mobility tasks. All participants stood for up to 30 s on firm and foam surfaces with eyes open then eyes closed, and performed the Timed Up and Go (TUG) test. Light weights (0.57–1.25 kg) were strategically applied to a vest‐like garment. Paired t tests compared within‐group differences with and without BBTW weights. Independent t tests assessed differences from controls. All t tests were one‐tailed with alpha set at .05. Results: Duration of standing for people with ataxia was significantly longer with weighting ( p = .004); all controls stood for the maximum time of 120 s with and without weights. More severe ataxia according to SARA was moderately correlated with greater improvement in standing duration with BBTW (Pearson r = .54). Tasks with more sensory challenges (eyes closed, standing on firm surface) showed less body sway with weighting. Duration for the TUG was unchanged by torso‐weighting in people with ataxia. Conclusion: Strategic weighting improved standing stability but not movement speed in people with ataxia. BBTW has potential for improving stability and response to challenging sensory conditions in this population. Future studies should further examine gait stability measures along with movement speed.